˝Odgovôri v celem stavku.˝ - Bešter, Marja (Jezik in slovstvo, 2014)
In grades 1-4 of primary school, pedagogical dialogue is characterised by, among other things, the teacher eliciting from the pupil syntactically complete, i.e., full sentences, in response to his or her questions, even if this means violating the rules of dialogical communication. The article presents the findings of research into how common this practice is in the classroom and how it is justified by the teachers who use it. This is followed by an interpretation of the answers in which we reflect on the (un)reasonableness of leading pedagogical dialogue in such a way.
Keywords: osnovnošolski pouk; komunikacija; skladenjsko popolni odgovori; učni pogovor; učiteljev govor; iščoči govor